2007
DOI: 10.1177/0013161x07311410
|View full text |Cite
|
Sign up to set email alerts
|

The Little District That Could: The Process of Building District-School Trust

Abstract: Purpose: This article describes how trust emerged as an issue in one school district and the processes by which central office administrators enhanced trust with its school site leaders.Method: This exploratory participant observer case study uses multiple sources of data including surveys, interviews, observations, and documents collected during a 4-year period from central office and school site leaders. Findings: The article illustrates how a university partner can play a critical role in surfacing and brin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 54 publications
(121 reference statements)
2
27
0
1
Order By: Relevance
“…The focus of this study is on school-level collective leadership development of both teachers and administrators. Certainly, district level leadership can be integral in the influence and development of school level leadership (Chhuon, Gilkey, Gonzalez, Daly, & Chrispeels, 2008; Mangin, 2009; Supovitz, 2006). Moreover, a perception of flatness or reduced hierarchy in district leadership can be beneficial for school improvement (Leithwood, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The focus of this study is on school-level collective leadership development of both teachers and administrators. Certainly, district level leadership can be integral in the influence and development of school level leadership (Chhuon, Gilkey, Gonzalez, Daly, & Chrispeels, 2008; Mangin, 2009; Supovitz, 2006). Moreover, a perception of flatness or reduced hierarchy in district leadership can be beneficial for school improvement (Leithwood, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Discussions related to the improvement of educational systems have drawn attention to the conditions inherent to educational reforms (Townsend, 2015). Specifically, authors have revealed a lack of relationships between schools and out-of-school organizations (Kolleck, 2016(Kolleck, , 2017, caused by a paucity of exchange beyond institutional borders (Chhuon et al, 2008). However, the structures of most education systems seem to discourage social exchange and interaction across institutional borders more than they encourage it.…”
Section: Trust Within Csas and Collaboration Network In Educationmentioning
confidence: 99%
“…As a result of the growing evidence with respect to the positive effects of collaboration in educational settings (e.g. Chhuon et al, 2008), scholars and practitioners have developed different initiatives with the aim to improve educational equality and interactions between schools and out-of-school organizations through fostering CSAs (Kolleck, 2019). Many different concepts have evolved in recent years to describe forms of collaboration in education.…”
Section: Trust Within Csas and Collaboration Network In Educationmentioning
confidence: 99%
“…They bridge critical boundaries between schools and the larger external context in which schools must adapt. District effectiveness research leans toward the view that actions, or in some cases inactions, by district leaders spread into schools in ways that affect teacher working conditions directly and student outcomes indirectly (Chhuon, Gilkey, Gonzalez, Daly, & Chrispeels, 2008; Diamond, 2012; Rorrer, Skrla, & Scheurich, 2008; Sharratt & Fullan, 2009; Trujillo, 2013). Districts can be highly centralized, loosely coupled, or somewhere in between (Firestone, 2009), and these organizational arrangements ultimately have differential consequences for school routines, processes, practices, and accomplishments.…”
Section: District Leadership and The Function Of Trustmentioning
confidence: 99%